PEREMPUAN DAN POLITIK: KEMENANGAN GUSTIMAR DALAM PEMILIHAN LEGISLATIF DPRD KABUPATEN SIAK PERIODE 2009-2019 - Kartika Fernandes; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Women and politics are a two-word series that is often used as a slogan by political parties ahead of elections. This slogan is intended for women to be interested in donating their votes to such political parties and this makes them indirectly exploited for electoral votes. In 2003, Law No.12 article 65 paragraph (1) on women's quotas was passed, stating that: "every political party of election participants can submit candidates for dprd, provincial parliament, and dprd district/city for each constituency with regard to women at least 30%". The study aims to describe the efforts made by Gustimar to face the 2009 Republican legislative elections, a strategy used by Gustimar to maintain his position as a member of the legislature in the 2014 election, looking at Gustimar's strategy to take office again in the period 2019-2024.This study used 2 (two) theories namely women and politics and political strategy theory. Startegi politics in 2 (two) namely offensive strategy and defensive strategy. Researchers use qualitative research methods that descriptively describe data. The data collection techniques used are interviews and documentation. While the data source used is primary data obtained from the research site in the form of research informants and further supported by secondary data in the form of data documents.The results of this study were found strategies and how to maintain the position of office that Gustimar gained from 3 (three) times this period by approaching nearby people such as family, relatives and neighbors, then forming a successful team to make the sound mapping more targeted, and target the votes obtained each period so that each period could improve the sound results. Keywords : women and politics, political strategy